More than a gut feeling – sonographic prenatal diagnosis of imperforate anus in a high‐risk population. (22nd August 2014) - Perlman, Sharon; Bilik, Ron; Leibovitch, Leah; Katorza, Eldad; Achiron, Reuven; Gilboa, Yinon
ABSTRACT Objectives The objective of this article is to investigate whether sonographic identification of the fetal anal mucosa (AM) can assist in the diagnosis of anal atresia (AA) in fetuses referred for congenital anomalies of kidney and urinary tract (CAKUT) malformation. Methods During a 3‐year study period, 245 fetuses referred for CAKUT were prospectively examined for the presence of the AM on an axial trans‐perineal view. The prenatal findings were confirmed clinically. Results The AM was identified in all but two fetuses. The diagnosis of AA was confirmed clinically. In two additional cases, the babies were born with imperforated anus. In the first case, the AM was identified prenatally. The baby was born with a thin membrane covering the anal pit, which was easily penetrated revealing a patent anal canal. The second case was a false–negative, in which the echogenic ischial tuberosity was falsely mistaken for the AM. None of the cases earlier had bowel dilatation or enterolithiasis. Overall, the incidence of AA in our group was 30‐fold relative to the general population (1.2% vs 0.04%). Conclusions In a CAKUT population, absence of the AM in the posterior perineal triangle in the axial trans‐perineal view emerges as an important sonographic marker for prenatal diagnosis of AA. © 2014 John Wiley & Sons, Ltd.